Exploring Foreign Language Enjoyment in Indonesian Higher Education: Insights from Non-English Major Students - Kurniawati, Lemmuela Alvita; Putra, Steven Sanjaya Pandji (UIR Press, 2026)
This study explores Foreign Language Enjoyment (FLE) in learning English among non-English major students in Yogyakarta, Indonesia, focusing on its level and contributing factors. Utilizing a mixed-methods approach, data were collected through a questionnaire adapted from Dewaele and MacIntyre (2014), distributed to 186 students across 27 universities/colleges, followed by semi-structured interviews with nine selected participants. Quantitative findings revealed a high overall FLE level (mean = 3.13 on a 4-point scale), with students reporting enjoyment in classroom activities, positive social interactions, and a supportive environment. Qualitative findings identified two main themes: (1) varied learning activities (e.g., creative tasks, English songs, and movie discussions) enhanced engagement, and (2) perceived safe classroom environment, characterized by non-judgmental feedback and peer support, fostered emotional security and participation. These findings highlight the importance of pedagogical diversity and emotional safety in promoting FLE, offering practical insights for educators to design enjoyable and inclusive language classrooms. It contributes to the underexplored context of non-English majors in Indonesia, emphasizing the interplay between instructional strategies and affective factors in language learning. Limitations include geographical and time constraints, suggesting future research to expand samples across regions and educational levels.